Karakteristik Komposit Bioplastik Pati Ubi Talas-Karagenan pada Variasi Suhu dan Waktu Gelatinisasi - Pujawati, Dewi; Hartiati, Amna; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 3 (2021): SeptemberDO - 10.24843/JRMA.2021.v09.i03.p02, 2021)
This study aims to determine the effect of variations in temperature and time of gelatinization on the characteristics of the bioplastic composite of taro starch-carrageenan and to obtain the right gelatinization temperature and time to produce a bioplastic composite of taro starch and carrageenan with the best characteristics. This study used a randomized block design with two factors. Factor one is gelatinization temperature which consists of 3 levels, namely 75±1 o C; 80±1 o C; 85±1 o C. Factor two is the gelatinization time for 3, 4, and 5 minutes. The observed variables included tensile strength, elongation at break, young modulus, water swelling, water vapor transmission rate (wvtr), and biodegradation. The data obtained were analyzed for diversity and continued with the BNJ. The results showed that variations in temperature and time of gelatinization and their interactions had a very significant effect on tensile strength and elasticity. Meanwhile, gelatinization temperature and time had a significant effect but did not interact with elongation at break. Moreover no significant effect on swelling, water vapor transmission and biodegradation. The best characteristics of bioplastic composites were found at a temperature of 85±1 o C and a gelatinization time of 5 minutes with a tensile strength value of 11,19 MPa, elongation at break 4,38%, modulus young 255,35 MPa, swelling 84,35%, water vapor transmission 0,55 g/h.m2 and the degradation time 7 days. Keywords : composites bioplastic, carrageenan, taro tuber starch, temperature and time of gelatinization